2021
DOI: 10.1101/2021.05.21.21257440
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

How COVID-19 challenged care for women and their newborns: a qualitative case study of the experience of Belgian midwives during the first wave of the pandemic

Abstract: In this article, we describe the results of a rapid qualitative study conducted between May 19 and June 25, 2020 on the work experience of midwives during the first wave of the COVID-19 pandemic in Brussels and Wallonia (Belgium). Using semi-structured interviews conducted with fifteen midwives working in hospitals or practicing privately, we investigated the impact of the first COVID-19 wave on their work experience, the woman-midwife relationship, and midwife-perceived changes in quality of care. Findings in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 13 publications
1
20
0
Order By: Relevance
“…Maternity skilled health personnel (SHP)—including doctors, nurses and midwives—were at the forefront of implementing these regularly updated guidelines and faced many challenges during the COVID-19 pandemic 3. In a global context of shortage of personal protective equipment (PPE), pre-existing shortage of SHP, and lack of clear information and guidelines,22 23 maternal and newborn SHP worried about their own health and were concerned over occupational exposure to COVID-19 in the workplace, and transmitting the infection to patients, family and friends 3 24–27. A meta-analysis shows that stress disorders, depression, anxiety, and insomnia are highly prevalent among SHP during periods of epidemics and pandemics, including COVID-19 28.…”
Section: Introductionmentioning
confidence: 99%
“…Maternity skilled health personnel (SHP)—including doctors, nurses and midwives—were at the forefront of implementing these regularly updated guidelines and faced many challenges during the COVID-19 pandemic 3. In a global context of shortage of personal protective equipment (PPE), pre-existing shortage of SHP, and lack of clear information and guidelines,22 23 maternal and newborn SHP worried about their own health and were concerned over occupational exposure to COVID-19 in the workplace, and transmitting the infection to patients, family and friends 3 24–27. A meta-analysis shows that stress disorders, depression, anxiety, and insomnia are highly prevalent among SHP during periods of epidemics and pandemics, including COVID-19 28.…”
Section: Introductionmentioning
confidence: 99%
“…These involve practising in different ways such as trying to maintain social distancing during face-to-face visits, replacing antenatal assessments with telehealth, and limiting postnatal care visits [11,12]. Other research has found that midwives have been confused with major discrepancies in guidelines between hospitals and the constant changing of the guidelines and the effect of COVID-19 on pregnant women [13]. Recent Australian research has shown that prior to the pandemic, midwives were facing both physical and emotional exhaustion, with high rates of stress and burnout, often related to their inability to provide woman-centred care within medical models [14].…”
Section: Introductionmentioning
confidence: 99%
“…However, they noticed that sometimes the quality of care was compromised [12]. In addition, qualitative studies from Belgium and Australia indicated that the midwives experienced high levels of stress because of the constantly changing measures and lack of resources which negatively affected the quality of care [13,14]. To provide a Dutch qualitative perspective, this study examined the experiences of Dutch midwives regarding the quality of care during the first two months of the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…However, they noticed that sometimes the quality of care was compromised [ 12 ]. In addition, qualitative studies from Belgium and Australia indicated that the midwives experienced high levels of stress because of the constantly changing measures and lack of resources which negatively affected the quality of care [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%